Toward high-current-density and high-frequency graphene resonant tunneling transistors - Zihao Zhang; Baoqing Zhang; Yifei Zhang; Yiming Wang; Patrick Hays; Seth Ariel Tongay; Mingyang Wang; Hecheng Han; Hu Li; Jiawei Zhang; Aimin Song (Nature Communications)
Abstract Negative differential resistance (NDR), a peculiar electrical property in which current decreases with increasing voltage, is highly desirable for multivalued logic gates, memory devices, and oscillators. Recently, 2D quantum-tunneling NDR devices have attracted considerable attention because of the inherent atomically flat and dangling-bond-free surfaces of 2D materials. However, the low current density of 2D NDR devices limits their operating frequency to less than 2 MHz. In this study, graphene/hexagonal boron nitride (h-BN)/graphene resonant tunneling transistors (RTTs) were fabricated using graphene and h-BN barriers with different numbers of atomic layers, showing a mechanism enabling the observation of NDR in high current density devices. A triangular etching approach was proposed to suppress the effects of graphene–metal contact resistance and graphene sheet resistance, enabling pronounced NDR effect even in a 2D tunneling device with a single atomic layer h-BN barrier. A room-temperature peak current density up to 2700 μA/μm2 and operational frequencies up to 11 GHz were achieved, demonstrating the potential of 2D quantum NDR devices for applications in high-speed electronics.